2018
DOI: 10.1080/00150193.2018.1499405
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast polarization switching of (BaSr)TiO3 thin film by a single-period terahertz pulse in a vicinity of phase transition

Abstract: Article 25fa pilot End User Agreement This publication is distributed under the terms of Article 25fa of the Dutch Copyright Act (Auteurswet) with explicit consent by the author. Dutch law entitles the maker of a short scientific work funded either wholly or partially by Dutch public funds to make that work publicly available for no consideration following a reasonable period of time after the work was first published, provided that clear reference is made to the source of the first publication of the work. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This is quite expected, since there is a component in the polarization that coincides with the direction of the terahertz field (in the film plane). On the other hand, three types of domains oriented at 120 degrees relative to each other can reduce the signal [ 51 ]. However, when considering terahertz excitation, we take into account the crystallography of the unit cell.…”
Section: Resultsmentioning
confidence: 99%
“…This is quite expected, since there is a component in the polarization that coincides with the direction of the terahertz field (in the film plane). On the other hand, three types of domains oriented at 120 degrees relative to each other can reduce the signal [ 51 ]. However, when considering terahertz excitation, we take into account the crystallography of the unit cell.…”
Section: Resultsmentioning
confidence: 99%
“…However, special attention should be paid to the size effects in these samples and their influence on the crystal structure [46,47]. I note that a 𝜋/2 polarization rotation induced by a strong single-cycle terahertz pulse in some domains of a multidomain ferroelectric thin film of (Ba 0.8 Sr 0.2 )TiO 3 , where the depolarized field should be reduced due to the natural shape of the domains, was claimed recently in [15][16][17].…”
mentioning
confidence: 85%
“…At the same time, the situation in ferroelectrics turned out to be more complicated [10]. The original proposal to switch the polarization by resonant excitation of the ferroelectric mode [11][12][13] has not yet been fully realized experimentally [14][15][16][17]. It was also shown that optical pumping with excitation of the electronic subsystem [18][19][20][21] leads only to a temporary decrease in polarization [22][23][24][25].…”
mentioning
confidence: 99%